If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 12) * 4 = 2x + -90 Reorder the terms: (12 + x) * 4 = 2x + -90 Reorder the terms for easier multiplication: 4(12 + x) = 2x + -90 (12 * 4 + x * 4) = 2x + -90 (48 + 4x) = 2x + -90 Reorder the terms: 48 + 4x = -90 + 2x Solving 48 + 4x = -90 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 48 + 4x + -2x = -90 + 2x + -2x Combine like terms: 4x + -2x = 2x 48 + 2x = -90 + 2x + -2x Combine like terms: 2x + -2x = 0 48 + 2x = -90 + 0 48 + 2x = -90 Add '-48' to each side of the equation. 48 + -48 + 2x = -90 + -48 Combine like terms: 48 + -48 = 0 0 + 2x = -90 + -48 2x = -90 + -48 Combine like terms: -90 + -48 = -138 2x = -138 Divide each side by '2'. x = -69 Simplifying x = -69
| 11(x-2)=99 | | 55x=935 | | 389+x=406 | | e(x+7)=30 | | 7(x-16)=287 | | (-9)(-12)= | | X+X^2+3x=54 | | x^2+2y^2-4x+8y+12=0 | | 3*(n+5)+12=26 | | X-2y-10=0 | | 5u-19=11 | | 2b+18-4b=60 | | N^2=11n | | 6+3(x-2)= | | 0=-2u-16 | | -7x+4(-3x-7)=-39-8x | | 93(6x4/8) | | 5log(7x+1)=10 | | .002x+.03=0.92 | | 5x=100/8.38 | | Z+14=30 | | 38+7k= | | 3a+5c=70 | | 5x=8.38/100 | | -2(-7x-7)=-84 | | x/8.38=5/100 | | -2(-7-7)=-84 | | 1/2x-3/4=1/3x+7/5 | | 2e^5=9 | | -8+1x= | | 3(8+6x)=240 | | 5/100=x/8.38 |